Stability analysis of lebesgue quadratic stochastic operator generated by 3-partition - Mohd Fadzullah, Nur Alis Aqeelah; Hamzah, Nur Zatul Akmar (Kulliyyah of Science, IIUM, 2023)
The work of Bernstein in 1924 by developing the theory of quadratic stochastic operator (QSO) has become the foundation of many researchers. The study of QSO can be divided into countable and continual state space. In this research, we introduce a new class of QSO on continual state space that is a construction of Lebesgue QSO generated by 3-partition with four parameters. The findings from this research may contribute to future studies of QSO, especially in the dynamic of Lebesgue QSO with different partitions and parameters.